Employee Mobility in UK Companies Operating in the Czech Republic Post-Brexit - Šestáková, Markéta (2025)
This thesis explores how Brexit has influenced employee mobility between the United Kingdom and the Czech Republic, focusing on UK companies operating in the Czech Republic. It investigates the staffing strategies and adaptations of Marks & Spencer, Tesco, Vodafone, and Shell in response to new post-Brexit regulations. Through interviews with HR professionals of these companies, the research reveals a variety of company responses, from minimal impact in companies already reliant on local talent to significant administrative burdens in those dependent on UK nationals. The research is supported by Human Capital Theory, Job Matching Theory, and Push-Pull Theory, which all offer insight into how regulation changes, cost considerations, and language requirements form employee mobility. While Brexit introduced new barriers, such as stricter visa requirements and relocation costs, companies responded with new strategies to be able to adapt. Despite persisting administrative challenges, companies that adapt flexibly continue working with international talent while strengthening local operations.